A functional polymorphism of microRNA-143 is associated with the risk of type 2 diabetes mellitus in the northern Chinese Han population - Kong, Dexian; Duan, Ya; Wang, Jinli; Liu, Yabin (Frontiers in Endocrinology, 2022)
Objective To explore the association between two polymorphisms of microRNA-143 (miR-143) and the risk of type 2 diabetes mellitus (T2DM) in the northern Chinese Han population. Study Design This case–control study involved 326 patients with T2DM and 342 healthy controls. Two genetic variants (rs4705342 and rs353292) of miR-143 were genotyped by the polymerase chain reaction/ligase detection reaction (PCR-LDR) method. The levels of miR-143 in the serum from 52 T2DM patients and 55 healthy subjects were investigated by quantitative real-time PCR (qRT–PCR). Results The CC genotype frequency of rs4705342 was significantly higher in the T2DM patients than in the healthy controls (P = 0.012). After adjusting for sex, age, and body mass index, the rs4705342 CC genotype was also related to a significantly increased risk of T2DM compared with the TT genotype (adjusted OR: 1.87; 95% CI = 1.09-3.19; P = 0.022). Stratified analyses demonstrated that T2DM patients with the rs4705342 CC genotype had significantly higher levels of low-density lipoprotein cholesterol (LDL-C), fasting blood glucose (FBG), and glycated haemoglobin (HbA1C) than those carrying the rs4705342 TT genotype. The qRT–PCR results showed that the expression levels of miR-143 were significantly higher in the serum of cases than in the serum of controls (P < 0.001). Furthermore, the levels of miR-143 were significantly higher in the serum of T2DM patients carrying the rs4705342 CC genotype than in those carrying the TC and TT genotypes of rs4705342 (P = 0.005 and 0.003, respectively). Conclusion The CC genotype of rs4705342 might be a risk factor for developing T2DM by increasing the expression of miRNA-143 in the northern Chinese Han population.